Association between single nucleotide polymorphism in miR-499, miR-196a2, miR-146a and miR-149 and prostate cancer risk in a sample of Iranian population - Mohammad Hashemi; Nazanin Moradi; Seyed Amir Mohsen Ziaee; Behzad Narouie; Mohammad Hosein Soltani; Maryam Rezaei; Ghazaleh Shahkar; Mohsen Taheri (2016)
MicroRNAs (miRNAs) play an important role in regulating gene expression at the post-transcriptional level and are involved in numerous physiological processes. Accumulating evidence suggests that single-nucleotide polymorphisms (SNPs) in human miRNA genes may affect miRNA biogenesis pathway and influence the susceptibility to several diseases such as cancer. The present study aimed to evaluate the impact of miR-499 rs3746444, miR-196a2 rs11614913, miR-149 rs2292832, and miR-146a rs2910164 polymorphisms on prostate cancer (PCa) risk in a sample of Iranian population. This case-control study was done on 169 patients with pathologically confirmed PCa and 182 benign prostatic hyperplasia (BPH). The genotyping assays were done using T-ARMS-PCR or PCR-RFLP methods. The findings indicated that CC genotype of miR-499 rs3746444 polymorphism increased the risk of PCa (OR = 1.76, 95% CI = 1.12-2.79, P = 0.019) compared to TT genotype. No statistically significant association was found between miR-196a2 rs11614913, miR-149 rs2292832, and miR-146a rs2910164 polymorphisms and PCa risk. In summary, the findings indicated that miR-499 rs3746444 polymorphism increased the risk of PCa in an Iranian population. Further studies with larger sample sizes and different ethnicities are necessary to verify the findings of the present study.